THE ROLE OF FOLK ORAL TRADITION IN CHILD EDUCATION (International journal of artificial intelligence, 2025)
Folk oral tradition is a rich heritage of Uzbek culture and plays an important role in the education of children. Through this creative heritage, children from an early age absorb national values, cultural heritage, moral concepts, and life lessons. Folk oral tradition is used to enhance the effectiveness and content of the educational process.